Hubungan Kebutuhan Spiritualitas dan Dukungan Keluarga dengan ADL (Activity Daily Living) pada Pasien Stroke yang Mengalami Gangguan Mobilitas Fisik - Ifa Mardhiyah; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (NAJ Nursing Applied Journal, 2025)
Stroke is a disease that causes stroke sufferers of depend on other people for ADL (Activity Daily Living). Family support is important for stroke sufferers so they don’t give up and can fulfill their spiritual needs. This research aims to analyze the relationship between spirituality needs and family support with ADL (Activity Daily Living). With this third factor, stroke patients can maintain optimal health. This research is descriptive research using a quantitative approach. The population of this study was 113 people. The sample used was 88 respondents using a cross sectional approach. Data were collected using the Daily Spiritual Experience Scale (DSES) questionnaire, the family support questionnaire, and the Bartel Index Questionnaire. Bivariate analysis test of the relationship between spirituality needs in stroke patients who experience impaired physical mobility using the gamma coefficient test obtained a p value of 0.040 and a correlation value (r) of 0.0338. The bivariate analysis test of the relationship between family support in stroke patients using the gamma coefficient test obtained a p value of 0.017 and a correlation value (r) of -0.468. There is a relationship between the need for spirituality and family support with ADL (Activity Daily Living) in stroke patients who experience impaired physical mobility at RSI Sultan Agung Semarang.